25(OH)D was Correlated with Increased Risk of Insulin Resistance, but Not Mediated by Adiponectin and hsCRP - Anggi Kartikawati; Yani Lina; Andi Wijaya (The Prodia Education and Research Institute (PERI), 2012)
BACKGROUND: Studies have shown that change of calcium and vitamin D homeostasis is associated with insulin resistance, decreased beta cell function, metabolic syndrome, glucose intolerance and diabetes. Evidence suggests that vitamin D insufficiency is inversely related to risk of metabolic disorders including type-2 Diabetes Mellitus (T2DM), although the underlying mechanisms are not yet understood. Hence, current study was conducted to investigate correlation between 25(OH)D and insulin resistance through adiponectin or High Sensitivity C-Reactive Protein (hsCRP) in centrally obese men.METHODS: This was a cross-sectional study involving 80 centrally obese men with waist circumference (WC) >90 cm and age 30-60 years. Total 25(OH)D concentration was measured by Enzyme-Linked Immunosorbent Assay (ELISA) method. Insulin resistance was calculated by HOMA model.RESULTS: This study showed there was no correlation of 25(OH)D-WC (r=0.006 and p=0.957), 25(OH)D-adiponectin (r=0.179 and p=0.111) abd 25(OH)D-hsCRP (r=-0.223 and p=0.334), but we observed statistically significant negative correlation between 25(OH)D and insulin resistance index (HOMA-IR) (r=0.461 and p=0.041).CONCLUSIONS: We conclude that low 25(OH)D concentration was significantly associated with increased risk of insulin resistance. Since the adiponectin or hsCRP was not correlated, the possible pathways need to be futher investigated.KEYWORDS: central obesity, 25(OH)D, adiponectin, hsCRP, insulin resistance (HOMA-IR)